2016
DOI: 10.1038/srep37534
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced vasculogenic mimicry formation in human colorectal cancer cells: Involvement of HIF-1a, Claudin-4, and E-cadherin and Vimentin

Abstract: Vasculogenic mimicry (VM) plays an important role in colorectal cancer (CRC) metastasis, and both hypoxia and the epithelial-mesenchymal transition (EMT) are necessary for VM. In this study, HIF-1α expression was upregulated in the VM-positive CRC cell line HCT-116 and thereby affected the expression of the EMT-related markers Claudin-4, E-cadherin (E-cd) and Vimentin(VIM). SB431542 and U0126EtOH, which can inhibit of EMT were used to treat HCT-116 and HCT-8 in these experiments. Both of the inhibitors had sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 22 publications
3
57
0
Order By: Relevance
“…1). This observation is in accordance with previous work by Li, et al, who reported particularly HIF-1α -induced vasculogenic mimicry formation in human colorectal cancer cells [30].…”
Section: Discussionsupporting
confidence: 94%
“…1). This observation is in accordance with previous work by Li, et al, who reported particularly HIF-1α -induced vasculogenic mimicry formation in human colorectal cancer cells [30].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, VM is associated with high tumor grade, invasion, metastasis, and poor prognosis in patients with malignant tumors [3][4][5][6]. In recent years, VM has been reported in a variety of malignant tumors, such as melanoma, glioblastoma, osteosarcoma, hepatocellular carcinoma (HCC), breast cancer, lung cancer, gastric cancer, colorectal cancer, and prostate cancer [7][8][9][10][11][12][13][14][15][16][17][18][19]. VM has emerged as a promising new target for anti-tumor therapy [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…7 VM had been found to evaluate in various aggressive cancers, including colorectal cancer, 8 breast cancer, 9 melanoma, 10 and head and neck squamous cell carcinoma, 11 suggesting that it was a novel hallmark of cancer. 17 Moreover, Ahluwalia et al reported that HIF-1 by hypoxia condition adjusted vascular endothelial growth factor A (VEGFA) expression at the transcriptional level. 12 Recently, increasing evidence has showed that hypoxic microenvironment not only accelerated tumour invasion and metastasis, but also led to VM formation 13,14 and the expression of hypoxia-inducible factor-1α (HIF-1α) was associated with VM in many cancers types, including breast cancer, 15 ovarian cancer 16 and colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%